Nutritional Requirement of Calcium in White Laying Hens from 46 to 62 Wk of Age - Narvaez-Solarte, William; Rostagno, Horacio Santiago; Soares, Paulo Rubens; Uribe-Velasquez, Luis F.; Silva, Marcelo A. (International Journal of Poultry Science, 2006)
A total of 240 Lohmann Selected Leghorn hens were fed 5 experimental diets in this experiment to determine dietary Ca requirement. Limestone was added to the basal diet containing 2800 kcal of ME/kg and 16.5% CP to produce 2.60, 3.00, 3.40, 3.80, and 4.20% Ca contents. This experiment lasted from 46 to 62 week of age. Increasing dietary Ca from 0.28 to 0.42% had a quadratic effect on egg production, egg mass, feed intake, feed conversion, and egg shell weight. With increasing dietary Ca bone strength linearly increased. Based on quadratic regression, dietary Ca requirements for maximum egg production and egg mass, and the best feed conversion were 3.52, 3.54, and 3.62%, respectively. Dietary Ca requirement for white laying hens from 46 to 62 weeks of age was 3.56% in the diet or 4.0 g Ca per hen daily with the average ambient temperature of 21.65oC.